High-resolution mapping defines the cooperative architecture of Polycomb response elements. - Orsi, G.A.; Kasinathan, S.; Hughes, K.T.; Saminadin-Peter, S.; Henikoff, S.; Ahmad, K. (Genome Research, 2014)
Polycomb-mediated chromatin repression modulates gene expression during development in metazoans. Binding of multiple sequence-specific factors at discrete Polycomb response elements (PREs) is thought to recruit repressive complexes that spread across an extended chromatin domain. To dissect the structure of PREs, we applied high-resolution mapping of nonhistone chromatin proteins in native chromatin of Drosophila cells. Analysis of occupied sites reveal interactions between transcription factors that stabilize Polycomb anchoring to DNA, and implicate the general transcription factor ADF1 as a novel PRE component. By comparing two Drosophila cell lines with differential chromatin states, we provide evidence that repression is accomplished by enhanced Polycomb recruitment both to PREs and to target promoters of repressed genes. These results suggest that the stability of multifactor complexes at promoters and regulatory elements is a crucial aspect of developmentally regulated gene expression.